A study about factors around alcoholic brand preference in South Africa - Mlatsha, Mbasa (The IIE, 2020)
In South Africa, the alcohol industry contributes largely to the growth of the economy (The South African Liquor Industry: our contribution, 2020). The study looks to uncover and identify factors surrounding alcohol brand preference in South Africa. The relevant to the ever-changing socio-economic sphere and lifestyles and relevant seeing there is an increase in the alcoholic brand pool. Interpretivism was the chosen research approach and it was supported with qualitative (which made up 70% of the research) and quantitative research (which made up 30% of the research). An online survey and a telephonic interview found that South Africans love gin and wine. The research showed South Africans purchase their favorite alcohol brands because of taste, price and quality (the main factor that influence their alcohol brand preference). With these findings, brands will understand their South African consumers to be able improve to themselves to satisfy the South African consumer.
Keywords: Liquor industry; Brands - alcohol; Marketing; Consumer behaviour; Brand identity